2010
DOI: 10.4212/cjhp.v63i6.959
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists Making House Calls:Innovative Role or Overkill?

Abstract: Background: The Medication Management Program was established at the Fraser Health Authority in 2005, in response to evidence suggesting that having pharmacists provide care to patients in their homes after discharge from hospital could reduce subsequent utilization of health service resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…14 Physician-led, team-based approaches combining advanced practitioners with pharmacists, nurses, and social workers are becoming a dominant mode of health care delivery associated with improved patient outcomes. [15][16][17] Previously, family medicine (FM) residents were required to complete at least 2 home visits during residency. In 2014, the Accreditation Council for Graduate Medical Education (ACGME) transitioned to a competency-based model, and no longer required completion of home visits.…”
Section: Introductionmentioning
confidence: 99%
“…14 Physician-led, team-based approaches combining advanced practitioners with pharmacists, nurses, and social workers are becoming a dominant mode of health care delivery associated with improved patient outcomes. [15][16][17] Previously, family medicine (FM) residents were required to complete at least 2 home visits during residency. In 2014, the Accreditation Council for Graduate Medical Education (ACGME) transitioned to a competency-based model, and no longer required completion of home visits.…”
Section: Introductionmentioning
confidence: 99%
“…Available studies have shown decreased health care utilization, decreased costs to the health system, and improved medication management with pharmacy involvement in home care. 6,7 Beneficial patient outcomes of pharmacy practice in home care settings, such as decreased hospital admissions, decreased emergency department visits, improved quality of life, improved compliance, and decreased adverse events, have been described in other developed countries. 8,9 In acute care settings, pharmacists improve a variety of patient outcomes, including mortality, length of stay, hospital readmissions, emergency department visits, medication errors, adverse drug events, and compliance.…”
Section: Résumémentioning
confidence: 99%
“…[13][14][15] The optimal service delivery model for pharmacists working in home care remains unclear; both home visits and telephonebased practices have been described. [6][7][8]16,17 Home care clinicians in the Winnipeg Regional Health Authority (WRHA) currently rely on community pharmacists for assistance with medicationrelated issues. Community pharmacists are limited in terms of the patient information that is available to them, which can affect their ability to make prescription changes.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacists' activities within the MMP include identifying and resolving drug-related issues, reconciling the medication regimen, providing patient education, organizing systems to enhance medication adherence, and removing expired, discontinued, or unused medications from the home. Economic and clinical evaluations of the MMP have been conducted 5,6 ; however, humanistic outcomes such as patient satisfaction have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%